POST-OPERATIV REHABILITATION OF THE JAWS AFTER ORTHOGNATHIC SURGERY - Dilkhumor G. Quranbaeva, (Central Asian Journal of Medicine, 2025)
Dental-jaw deformities, resulting from congenital, developmental, or traumatic factors, can significantly impact both functional and aesthetic aspects of patients’ lives. Surgical interventions to correct these deformities are essential, but the recovery process often demands a comprehensive rehabilitation approach to ensure long-term success. This study focuses on the development and implementation of rehabilitation measures aimed at improving post-surgical outcomes for patients undergoing corrective surgery for dental-jaw deformities. A multidisciplinary rehabilitation protocol was designed, integrating physical therapy, speech therapy, and orthodontic interventions. This study included 20 patients who had undergone various surgical procedures, including orthognathic surgery and mandibular realignment. Rehabilitation began 1 weeks post-surgery, with patients receiving personalized treatment plans based on their specific deformity and surgery type. Outcome measures included functional improvements (jaw mobility, bite efficiency), aesthetic satisfaction, and psychological well-being, assessed at baseline, and month after the surgery.